Traffic Management Analysis on the Bunggasi Road Section of Kendari City - Makmur, Muzammil; Makmur, Muammar (Jurnal Multidisiplin Indonesia, 2025)
City which is located in the Andounohu area. Based on the spatial map of the CBD area of Kendari City where the dominant activity that occurs on the road is economic activities which are marked by rows of Shop Houses (Shophouses), Markets, Mosques, Banks, Restaurants and so on. One of the factors that causes changes and increases in the shape of the area on this road is the existence of Marina Mart shopping centers and Anduonohu Market. The research "Traffic Management Analysis on Jl.Bunggasi Section" is located along the Bunggasi road, Kendari City, Southeast Sulawesi. Point zero is in front of the "Ayam Geprek Bosqu" Restaurant to the front of the HBM Store which is approximately 1.09 Km away. The performance of the Bunggasi road section in 2024 has the highest saturation degree of DJ (Saturation degree) on busy days of 0.41 which is included in the service level B, and on holidays it is 0.48 which is included in the road service level with category C. Based on the results of field findings through observations and traffic surveys conducted in the study of traffic engineering management on the Bunggasi Road section is the high volume of traffic during peak hours of activity and The small capacity of the road section is due to the parking on street and also due to the U-turn which causes congestion on the Bunggasi road section.